Compressive strength of geopolymer with recycled carbon fibres manufactured in air and in water by casting and additive manufacturing - Denker, Meike; Gharehpapagh, Bahar; Gruhn, Richard; Pose, Sebastian; Korniejenko, Kinga; Grab, Thomas; Zeidler, Henning (Frontiers in Built Environment, 2025)
Geopolymers (GPs) are inorganic binders synthesised from reactive aluminosilicate materials such as metakaolin, fly ash, and blast furnace slag, using strongly alkaline solutions at room temperature. They are more environmentally friendly than Portland cement and exhibit high hardness, weathering resistance, thermal stability, and precise mouldability. These properties make them suitable for additive manufacturing (AM) and specialised underwater applications, such as encapsulating hazardous substances or stabilising corroding shipwrecks. This study investigates the compressive strength of metakaolin-based GP reinforced with recycled carbon fibres, comparing performance in different water environments over time. Samples were produced by mould casting in air, manual underwater extrusion, and AM via material extrusion with chemical reaction bonding (MEX-CRB) in air. The 3D-printed and mould-cast samples produced in air were stored for up to 3 months in different water environments with varying salt and mineral contents to assess durability, mechanical performance, and environmental impact at defined intervals. For manually printed underwater specimens, the storage period was extended to almost 6 months, with only conducted in tap water conditions. Mould-cast specimens in air reached ∼50 MPa, while MEX-CRB samples achieved ∼20 MPa; after 3 months in salt water, mould-cast samples retained ∼30 MPa, whereas printed ones remained below 20 MPa. Manually printed underwater samples increased from ∼8 MPa at casting to ∼14–15 MPa by week 4 before stabilizing. Microstructural observations showed crack-bridging by fibres, with random orientation in cast samples improving isotropic strength, while fibre alignment and higher porosity in printed samples limited performance. The water analysis results underscore the environmentally friendly potential of GPs in reducing environmental risks and developing sustainable methods for underwater construction and hazard prevention.